Glutamate modulators in the treatment of obsessive-compulsive disorder - Pittenger, Christopher (Psychiatr Ann, 2015)
Established treatments for obsessive-compulsive disorder (OCD) are of benefit in approximately 3 of every 4 patients, but refractory disease remains distressingly common, and many treatment responders continue to experience considerable morbidity. This motivates a search for new insights into pathophysiology that may inform novel treatment strategies. Much recent work has focused on the neurotransmitter glutamate. Several lines of neurochemical and genetic evidence suggests that glutamate dysregulation may contribute to OCD, although much remains unclear. The off-label use of a number of pharmacological agents approved for other indications has been investigated in refractory OCD. We summarize investigations of memantine, riluzole, ketamine, D-cycloserine, glycine, N-acetylserine, topiramate, and lamotrigine. Evidence exists for benefit from each of these in some patients; though none has been proven effective with sufficient clarity to be considered part of standard care, these agents are options in individuals whose symptoms are refractory to better-established therapeutic strategies.